Analisis Wacana Kritis Sara Mills dalam Cerpen Sepasang Mata Dinaya yang Terpenjara - Wiwit Sariasih; Yumna Rasyid; Miftahulkhairah Anwar (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2023)
This research aims to describe the subject-object and writer-reader positions in the short story "Sepasang Mata Dinaya yang Terpenjara" by Ni Komang Ariani. This research is qualitative descriptive research. The subject of this research is the storyteller, who is the one who tells the story to the reader. The object of this research is how Diyana's position as a child from childhood has been positioned as a person who only accepts reproaches from her mother without resistance and how her position in her husband's eyes is not considered her presence. This research data was collected by analyzing short stories published in Kompas newspaper on May 20, 2010, using Sara Mills' critical discourse analysis. This research's instrument is the researcher who captures the language style conveyed in the short story. The results of this study show how the subject-object position in the story where the object of the story is more likely to accept her condition, although there is a little resistance but only in his mind. While the subject-object position here is that the subject leads the reader to accept the author's ideas and sympathize with the object.